Superfluid Helium cooling and compact Heat Exchanger for HL-LHC D2 Recombination Dipoles. (April 2019) - Rousset, B; Bancel, F; Claudet, S; Millet, F; Nivelon, P; Perin, A; Van Weelderen, R
Abstract: New D2 recombination dipoles with a larger aperture than in the LHC dipoles are required for the futureH ighL uminosity LHC at CERN. These 13.5 m-long D2 magnets are proposed to be conduction cooled in a static bath of pressurized He II. Their cooling is provided via pressurized He II channels located in the D2 iron yoke and thermally connected to a saturated bath installed at one end of each D2 dipole. The heat transfer between the pressurized He II static bath and the bath pumped down to 16.4 mbar (1.8 K) is performed in a heat exchanger under study at CEA. Various design solutions were studied and evaluated to define the more suitable solution fulfilling on the one hand D2 cooling requirements (up to 70 W) and on the other hand D2 cryostat integration constraints. The paper will report on the D2 cooling needs and constraints, present the studied options and detail the main design features of the selected solution for a compact heat exchanger for D2 dipoles.